2013
DOI: 10.3174/ajnr.a3608
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Functional Network Connectivity among Resting-State Networks in Children with Frontal Lobe Epilepsy

Abstract: BACKGROUND AND PURPOSE:Epilepsy is considered a disorder of neural networks. The aims of this study were to assess functional connectivity within resting-state networks and functional network connectivity across resting-state networks by use of resting-state fMRI in children with frontal lobe epilepsy and to relate changes in resting-state networks with neuropsychological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 40 publications
6
54
0
3
Order By: Relevance
“…FLE, frontal lobe epilepsy. association with impaired motor function (Widjaja et al, 2013). Our findings also extend upon previous studies of temporal lobe epilepsy patients, where reduced connectivity within memory networks was correlated with poorer memory test scores (Doucet et al, 2012), and decreased connectivity within language networks provided a possible explanation for patients' language impairments (Waites et al, 2006).…”
Section: Motor Impairments and Resting-state Connectivitysupporting
confidence: 84%
See 3 more Smart Citations
“…FLE, frontal lobe epilepsy. association with impaired motor function (Widjaja et al, 2013). Our findings also extend upon previous studies of temporal lobe epilepsy patients, where reduced connectivity within memory networks was correlated with poorer memory test scores (Doucet et al, 2012), and decreased connectivity within language networks provided a possible explanation for patients' language impairments (Waites et al, 2006).…”
Section: Motor Impairments and Resting-state Connectivitysupporting
confidence: 84%
“…Functional connectivity changes in attention and auditory resting-state networks of the frontal lobe were also associated with age at seizure onset in children with FLE. Specifically, weaker connectivity was seen in auditory networks, and stronger connectivity in attention networks, in children who had seizures beginning at an earlier age (Widjaja et al, 2013). However, no associations were found between connectivity in the sensorimotor network and age at seizure onset, or duration of epilepsy (Widjaja et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The presence of slow fluctuations at frequencies between 0.01 and 0.1 Hz in brain regions involved in sensory, motor, visual, auditory, language and attention processing. These coordinated brain signals have shown to be robust and consistent across various functional imaging techniques such as fMRI (Biswal et al, 1995), optical imaging (Arieli et al, 1996), positron emission tomography (PET) (Raichle et al, 2001), electrophysiology (Laufs et al, 2003, Leopold et al, 2003 Several studies have revealed disturbances in RSNs in different types of epilepsy, including MTLE (Widjaja et al, 2013, Cataldi et al, 2013. These RSN changes may be linked to inter-ictal cognitive impairment.…”
Section: Introductionmentioning
confidence: 96%